A model for prevocational training of specialists: managing the “Media class in Moscow schools” project as an example of implementing state and municipal education policy - Andrey V. Sazonov; Alexandrina A. Svetlova; Sergey V. Morozov (RUDN Journal of Public Administration, 2025)
The study presents an analysis of the development of pre-professional education in Moscow with an emphasis on the implementation of the Media Class in a Moscow School project, which has become an example of successful integration of media technologies into the educational process. Key management decisions are considered, such as standardization of educational routes, development of specialized and additional teaching aids and programs, as well as interaction of schools with universities and enterprises. Particular attention is paid to the increasing role of municipal support, which ensures the unity of educational approaches and coordination of actions between educational institutions and external partners. The authors study the educational needs and interests of students in media classes of Moscow schools based on the results of the survey. The main areas of study in demand among schoolchildren are identified, including media production, journalism, photo, and video shooting. The authors conclude that the practice-oriented approach to learning, which involves participation in specialized courses and interaction with the professional environment helps to develop the necessary competencies in schoolchildren to work in the media industry. The study presents a model of comprehensive student training based on the integration of theoretical knowledge and practical skills. The importance of project activities and an interdisciplinary approach that promote critical thinking, creativity and career guidance is emphasized. The authors conclude that it is important to consolidate the efforts of government agencies, educational institutions and industry partners to further train highly qualified specialists who can adapt to the requirements of the digital economy. The study emphasizes the need for further research into the long-term impact of pre-professional education on the career prospects of media class graduates.